Peran Local Celebrity Endorsement Pada Iklan di Media Sosial Terhadap Pembelian Produk Kuliner di Provinsi Bali Pada Masa Stay Home Akibat Pandemi Covid-19 - Wijaya, Putu Yudy; Suasih, Ni Nyoman Reni (JURNAL BISNIS STRATEGI, 2020)
The pandemic of COVID-19 takes the community to do physical distance and do more activities at home (stay home). More is expelled from work, more than people working in the tourism sector, such as in Bali. Many are turning from jobs to culinary traders because they think the sector is still waiting for a pandemic, and they are using online marketing techniques through local celebrity support services. The purpose of this study was to analyze the influence of local celebrity endorsement through social media on buying interest, impulsive buying, and consumer loyalty of culinary products during their stay at home during the COVID-19 pandemic. This study was conducted on consumers of culinary products in Bali. Data were collected using an online questionnaire instrument for 174 respondents. The analysis technique uses SEM-PLS. The analysis shows that local celebrity support directly influences significantly on buying interest, and indirectly influences significance on impulsive buying and consumer loyalty of culinary products.